Stories of a fat ballerina (DAPesquisa, 2020)
This text presents a collection of fragments about the artistic-academic research of fat ballerina Jussara Belchior. The writing deals with issues, discussions and intersections of the fat phobia as the choreographic creation of the solo piece Peso Bruto (2017), the notion of fat representation, experiences of invention and reflection on the ways of doing (art and research), a fat reference that crosses several fields of knowledge, informations constituted by the proposition that the personal is political, by Carol Hanisch and a gross writing that takes place through the author's dance practice procedures.
Keywords: Writing and art; Performative (Philosophy); Discrimination against overweight persons; Performance art